Regulation of Gut Microbiota on Immune Reconstitution in Patients With Acquired Immunodeficiency Syndrome - Geng, Shi-Tao; Zhang, Zun-Yue; Wang, Yue-Xin; Lu, Danfeng; Yu, Juehua; Zhang, Jian-Bo; Kuang, Yi-Qun; Wang, Kun-Hua (Frontiers in Microbiology, 2020)
Human immunodeficiency virus type 1 (HIV-1) infection of CD4+ T cells in the gut plays an insidious role in acquired immunodeficiency syndrome (AIDS) pathogenesis. Host immune function is closely related to gut microbiota. Changes in the gut microbiota cause a different immune response. Previous studies revealed that HIV-1 infection caused changes in gut microbiota, which induced immune deficiency. HIV-1 infection results in an abnormal composition and function of the gut microbiota, which may disrupt the intestinal epithelial barrier and microbial translocation, leading to long-term immune activation, including inflammation and metabolic disorders. At the same time, an abnormal gut microbiota also hinders the effect of antiviral therapy and affects the immune reconstruction of patients. However, studies on the impact of the gut microbiota on immune reconstitution in patients with HIV/AIDS are still limited. In this review, we focus on changes in the gut microbiota caused by HIV infection, as well as the impact and regulation of the gut microbiota on immune function and immune reconstitution, while we also discuss the potential impact of probiotics/prebiotics and fecal microbiota transplantation (FMT) on immune reconstitution.